THE INFLUENCE OF ENVIRONMENTAL BELIEFS, ATTITUDES, MORAL OBLIGATIONS, AND SUBJECTIVE NORMS ON GREEN CONSUMER BEHAVIOR IN SURABAYA’S STAR HOTELS - Panjaitan, Thyophoida Wanty Suriany ; Indrawati, Lilik; Christian, Allen (Catholic University Musi Charitas, 2025)
Purpose: This study aims to analyze the influence of environmental beliefs, attitudes, moral obligations, and subjective norms on green consumer behavior among hotel visitors in Surabaya. Design/Methodology/Approach: The research employed a quantitative approach using a survey method. A total of 100 respondents who had stayed at star-rated hotels in Surabaya were selected as the sample. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings: The results indicated that environmental beliefs significantly influenced attitudes, and moral obligations significantly influenced subjective norms. Furthermore, both moral obligations and subjective norms had a significant influence on green consumer behavior. However, attitudes and environmental beliefs did not have a significant direct effect on behavior. Practical Implications: The findings highlight the importance of enhancing tourists’ moral awareness and leveraging social norms to promote environmentally responsible behavior in the hospitality industry. These insights can be utilized by hotel managers and tourism policymakers to design sustainability-based campaigns and service standards. Originality/Value: This study contributes to the understanding of pro-environmental consumer behavior in the tourism sector by integrating psychological constructs such as moral obligation and subjective norms into a green behavior framework, particularly within the context of developing countries.